Tom 3: variety of sweet sorghum for the production of high quality forage in Durango - Jiménez Ocampo, Rafael; Rosales Serna, Rigoberto; Domínguez Martínez, Domínguez Martínez; Cuéllar Robles, Evenor Idilio (Revista Mexicana de Ciencias Agrícolas, 2024)
Sorghum varieties and seed are required to supply the demand for high-quality forage in Durango. The objective was to develop a variety of sorghum adapted to irrigated and rainfed conditions to produce high-quality forage. The variety Tom 3 (OM-1 m-2 m-3 u) was generated by mass selection from the population collected in Otilio Montaño, San Juan del Río, Durango. This variety exceeded the state average yield (32.7 t ha-1), with an average fresh forage yield of 55 t ha-1. The Tom 3 variety, compared to Mercedes (control), had more days to the emergence of the panicle (93 vs 81 days after sowing: DAS), height at cut maturity (297 vs 256 cm) and very low weight of 1000 seeds (12.8 g vs 17.4 g). Tom 3 is recommended for the production of forage (fresh and silage) and bioethanol. The caryopsis is orange in color and shows a very long grain surface covered by the glume. Tom 3 is resistant to ergot (Claviceps spp.) and susceptible to lodging (70%) in some cases. Tom 3 is in the process of being validated to establish its adaptability and potential to increase the yield and quality of forage produced in Mexico.
Keywords: Sorghum bicolor; adaptation; attributes; productivity